EFFECTS OF SERVICE QUALITY MANAGEMENT ON COMPETITIVE ADVANTAGE OF TELCOMMINICATION INDUSTRY IN MOGADISHU SOMALIA - YUSUF, HUSSEIN HASSAN; THEURI, Dr FRIDAH (IJRDO - Journal of Business Management, 2016)
The general objective of this study was to investigate the service quality management on competitive advantage on mobile telephone providers in Somalia with specific focus of the industrial mobile providers in Somalia . Specifically, this study investigated the effects service quality on competitive advantage on mobile providers in Somalia . The study employed a survey research design in data collection. This research employed quantitative data collection method whereby data was gathered by the use of closed ended questionnaires which were self administered. Factor analysis was used to assess the validity and Cronbach alpha to assess reliability of the questionnaire. Multiple regression analysis (standard and step wise) were conducted to determine the effects between the service quality determinants and competitive advantage. Results confirm the varying importance of service quality determinants in the telephone providers processing in Somalia. In general, the results reveal that customer loyality,price fairness and brand image have significant and positive effects on competitive advantage in the mobile providers in Somalia. The study recommends that to improve customer satisfaction in the mobile providers in Somalia , managers of the industrial mobile providers in Somalia should nurture and develop market competition and customer satisfaction The general objective of the study is to investigate the effects service quality management on competitive advantage mobile providers in Mogadishu. Specifically, this study investigated to ascertain how customer loyalty mgt affects, price fairness affects and brand image on competitive advantage mobile providers in Mogadishu Somalia The study employed a survey research design in data collection. This research employed quantitative data collection method whereby data was gathered by the use of closed ended questionnaires which were self administered. Factor analysis was used to assess the validity and Cronbach alpha to assess reliability of the questionnaire. Multiple regression analysis was performed to assess the relationship between the dependent variable (value addition) and the independent variables (customer loyalty mgt, price fairness and brand image) and to test the research hypotheses on the service quality mgt determinants of competitive advantage in the mobile providers in Somalia with specific focus on Mogadishu The study recommends that to improve competitive advantage in mobile industry Mogadishu Somalia, managers of mobile industry Somalia in Mogadishu should nurture and develop customer loyalty and price fairness